Motivasi Kerja Pustakawan Di UPT. Perpustakaan UIN Ar-Raniry Banda Aceh - T. Mulkan Safri; Cut Raihan Miski (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Motivation is formed from human needs, how behavior can be initiated and directed. Work motivation is important for librarians in working in the library. In this study the author aims to determine how work motivation and the factors that encourage work motivation of librarians at UPT. UIN Ar-Raniry Library Banda Aceh. The research method used is descriptive qualitative research. Data collection techniques used by interviews, observation and documentation. Researchers conducted interviews with 7 informants who were selected based on purposive sampling technique. The results of this study are librarians at UPT. UIN Ar-Raniry Banda Aceh Libraries have motivations that arise within themselves, both intrinsic motivation and extrinsic motivation, work motivation related to responsibilities as a librarian profession, working to meet the needs of life, working to get achievement, and work motivation that related to trying to give the best work. There are factors that influence the work motivation of librarians such as income in the form of rights or benefits, a comfortable and safe work environment, social needs and opportunities for growth. Things that can increase the motivation of librarians in working at the UIN Ar-Raniry Library, namely by fulfilling the responsibilities given, improving the quality and existing competencies. As well as the obstacles faced due to the lack of ability of librarians to do something new and difficult to deal with visitors with various characters.